Application of Digital Media and Deep Learning to Hydrocarbon Materials at the High School Level: Systematic Literature Review - Syifaul Auliya; Sri Handayani (Indonesian Journal of Chemical Education, 2025)
This study aims to analyze the use of digital media and deep learning learning on hydrocarbon materials and their derivative compounds at the high school level through the Systematic Literature Review (SLR) approach. The study was conducted by analyzing various journals from Scopus and Google Scholar data using the keywords "digital media", "deep learning", "hydrocarbon compounds", "SMA", and "Indonesia". Of the 127 articles found between 2010–2025, only five met the inclusion criteria, namely research conducted in Indonesia using quantitative methods in the context of high school chemistry learning. The analysis shows that the use of digital media such as interactive simulations, animated videos, and games significantly improves student learning outcomes and motivation. In addition, the deep learning approach also contributes to improving students' critical and analytical thinking skills, although its implementation is still hampered by infrastructure problems and teacher readiness. Overall, digital media and deep learning have proven to be effective in improving students' conceptual understanding and engagement in chemistry learning. This study recommends the development of an interactive digital media-based learning model with a deep learning approach to evaluate its effectiveness in the long term.